Handling low hemoglobin and iron deficiency in a blood donor population: 2 years' experience. Issue 10 (18th May 2015) - Magnussen, Karin; Ladelund, Steen
<x xml:space="preserve">Abstract</x> BACKGROUND Iron deficiency and blood donors with low hemoglobin (Hb) concentration are well‐known challenges in any blood bank setting. In the Capital Region of Denmark, a new approach was adopted that centralized measurement of Hb, initiated ferritin (F) measurement, and established a center for donor Hb and iron. An algorithm was created based on Hb and F levels, which drove decisions on outreach by the donor Hb and iron resource team to the donor, including whether to provide iron supplementation or, on rare occasions, a referral to the donor's general practitioner. STUDY DESIGN AND METHODS The change in Hb for repeat donors was followed during the first 2 years of the intervention strategy, which included measurements of F and offering intermittent iron supplementation to some of the donors. RESULTS In 2 years, 62, 663 blood donors donated 193, 288 units of blood and 318 donors gave 754 complete blood count blood samples. Over time in the repeat donors, the Hb increased from 15.39 to 15.60 g/dL and 13.85 to 14.06 g/dL in male and female donors, respectively, and the proportion of donors with low Hb decreased from 0.9% to 0.3% and 3.9% to 2.7% for the male and female donors, respectively. CONCLUSION The program with goal‐directed iron supplementation only to those that would benefit has led to an increase in Hb concentration and a reduction in the proportion of donors with low Hb concentration.